Controllable high-performance memristors based on 2D Fe2GeTe3 oxide for biological synapse imitation. (19th May 2021) - Zeng, Xiangyu; Huang, Shuyi; Ye, Qikai; Rajagopalan, Pandey; Li, Wei; Kuang, Haoze; Ye, Ge; Chen, Chufan; Li, Menglu; Liu, Yulu; Shi, Lin; Guo, Yuzheng; et al.
Abstract: Memristors are an important component of the next-generation artificial neural network, high computing systems, etc. In the past, two-dimensional materials based memristors have achieved a high performance and low power consumption, though one at the cost of the other. Furthermore, their performance can not be modulated frequently once their structures are fixed, which remains the bottleneck in the development. Herein, a series of forming free memristors are fabricated with the same Cu/Fe3 GeTe2 oxide/Fe3 GeTe2 /Al structure, yet the On/Off ratio and set voltage is modulated continuously by varying the oxidation time during fabrication. With an optimal oxidation time, a large On/Off ratio (1.58 × 10 3 ) and low set voltage (0.74 V) is achieved in a single device. The formation and rapture of Al conductive filaments are found to be responsible for the memristors, and the filaments density and the cross-section area increase with the increase of current compliance, which achieves a higher On/Off ratio. The memristor can imitate basic biological synaptic functions using voltage pulses, demonstrating the potential for low-power consuming neuromorphic computing applications.